Tornado from SGS LTER HQ - Lindquist, Mark, photographer (Colorado State University. Libraries, 2010)
Wide view of tornado and SGS LTER manager's house on May 18, 2010, seen from SGS LTER HQ.
Keywords: SGS; tornado; weather